Epistemologis Tafsir Tematik: Menuju Tafsir Al-Qur’an Yang Holistik - Fajri Kamil; Pathur Rahman; Sulaiman Mohammad Nur; Deddy Ilyas (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The aim of this research is to discuss the Epistemological Efforts of Thematic Interpretation in Holistic Interpretation of the Qur'an. This research falls under the category of qualitative research, therefore the researcher only conducts a literature review. The first step involves gathering literature sources, both primary and secondary sources. The next step in this research is to provide a description of the literature sources that discuss the history, meaning, principles, and steps of thematic interpretation. The conclusion of this research is obtained through an analysis or epistemological approach to the method of thematic interpretation. The results and discussions of this research reveal that the discourse on the thematic method among scholars and scientists has led to the development of this method through the collaboration of modern scientific knowledge in the field of interpretation. This collaborative interpretation is referred to as integrative thematic interpretation, which enhances the existing classification of thematic interpretation. Ideally, all classifications of thematic interpretation can be interwoven into an integrative formulation of thematic interpretation, thus resulting in a holistic thematic interpretation of the Qur'an. Holistic thematic interpretation of the Qur'an is an epistemological effort to establish the validity of interpretation as a divine truth and as a rational and sensory truth that can be justified apriori, aposteriori, and pragmatically. Keywords: qur’an; thematic interpretation; epistemological; holistic.